2020
DOI: 10.1038/s41419-020-2618-6
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-mediated repression of SLC7A11 drives vulnerability to GPX4 inhibition in hepatocellular carcinoma cells

Abstract: System x c − contributes to glutathione (GSH) synthesis and protects cells against ferroptosis by importing cystine and exchanging it with glutamate. Transforming growth factor β1 (TGF-β1) induces redox imbalance; however, its role in system x c − regulation remains poorly understood. The present study was the first to show that TGF-β1 repressed the protein and mRNA levels of xCT, a catalytic subunit of system x c − , in PLC/PRF/5, Huh7, Huh6, and HepG2 cells with an early TGF-β1 gene signature but not in SNU3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 37 publications
2
92
2
Order By: Relevance
“…The results found with TGF-β1 stimulation in this study were comparable to the features found in kidney tubular cells treated with the positive control ferroptosis inducer Erastin, suggesting that ferroptosis may be induced in kidney tubular cells under diabetic conditions. These results are in line with a recent investigation which has shown that TGF-β1 represses xCT expression via Smad3 activation, and enhances lipid peroxidation in hepatocellular carcinoma cells 40 . Since TGF-β1 is known to increase reactive oxygen species production 41 , the accumulation of oxidative stress through TGF-β1 stimulation may lead to ferroptosis development.…”
Section: Discussionsupporting
confidence: 92%
“…The results found with TGF-β1 stimulation in this study were comparable to the features found in kidney tubular cells treated with the positive control ferroptosis inducer Erastin, suggesting that ferroptosis may be induced in kidney tubular cells under diabetic conditions. These results are in line with a recent investigation which has shown that TGF-β1 represses xCT expression via Smad3 activation, and enhances lipid peroxidation in hepatocellular carcinoma cells 40 . Since TGF-β1 is known to increase reactive oxygen species production 41 , the accumulation of oxidative stress through TGF-β1 stimulation may lead to ferroptosis development.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, ferroptosis, a biological process in which immune therapy and sorafenib converge to exert an anti-tumor effect, might have a fundamental impact on the treatment response of HCC. The understanding of the occurrence and regulation of ferroptosis has increased considerably in recent decades; however, only a few studies have explored the ferroptosis-related genes (FRGs) and pathways in HCC ( Louandre et al, 2013 , 2015 ; Carlson et al, 2016 ; Houessinon et al, 2016 ; Sun et al, 2016b ; Bai et al, 2019 ; Qi et al, 2019 ; Feng et al, 2020 ; Kim et al, 2020 ). With the currently available FRGs and immune-related genes (IRGs), and the accumulative data deposited in public databases like The Cancer Genome Atlas (TCGA), it is hypothesized that a prognostic molecular classifier based on the immune response and ferroptosis status might help to identify subgroups of HCC patients with distinct ferroptosis-immune phenotypes and survival profiles.…”
Section: Introductionmentioning
confidence: 99%
“…It scavenges free radicals and maintains the redox balance inside and outside the cell ( 59 ). SLC7A11 is highly expressed in a variety of tumors; by increasing cystine uptake it leads to increased intracellular GPX4 synthesis, reduced intracellular oxidative stress and the suppression of ferroptosis, thereby promoting tumor growth ( 60 , 61 ). GPX4 is a GSH-dependent enzyme, and selenocysteine, which is one of the amino acids in the active center of GPX4, can be inserted into GPX4 through selenocysteine transfer RNA (tRNA) ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%